Enhancement of Productivity to Improve Indonesia’s Labor Competitiveness - Rivani, Edmira (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The Covid-19 pandemic-induced economic crisis has affected labor in Indonesia. A number of workers have been laid off, as the crisis has caused disruption to companies’ operations. Labor is critical to the economic development process. Along with infrastructure and governance, labor is a critical factor that can drive and accelerate an economy’s decline in competitiveness. Several empirical studies have found a strong relationship between labor and economic competitiveness. The more competitive the labor market of a country, the more competitive the country’s economy, and vice versa. Increasing labor competitiveness is the result of a time-consuming process of structured and systematic human resource development. This study will describe the issues that must be addressed in human resource development in Indonesia, as well as some steps that can be taken to improve it. According to statistical data, Indonesia’s human resource development lags behind that of several competing countries, including those in the ASEAN region. It is understandable that human resource development in this country has not made a significant contribution to and has not been optimally correlated with increased productivity. Improving the design and implementation of skills improvement policies is critical as part of efforts to increase competitiveness and labor productivity